Prescribed norms : women and health in Canada and the United States since 1800 - Warsh, Cheryl Krasnick, 1957- (Toronto : University of Toronto Press, 2010)
"By comparing ritual practices of various cultures, Prescribed Norms demonstrates how looking at women's health through a masculine lens has distorted current medical understandings of menstruation, menopause, and childbirth, and has often led to faulty medical conclusions. Warsh also illuminates how the shift from informal to more formal, institutionalized treatment impacts both women's health care and women's roles as health practitioners"--Pub. info
Part I, Rituals. Wendy's last night in the nursery : the "disease" of menstruation and its treatment ; Gladys, take your medicine! The culture and business of menopause -- Part II, Technologies. Traditional childbirth : mothers and babies ; Modern childbirth : mothers and doctors ; Future childbirth : doctors and babies -- Part III, Professions. Networks of support, networks of opposition : the medical education of women ; Nursing : the science of womanly arts -- Epilogue : the case for chaos.
Includes bibliographical references (pages 275-303) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Women -- Health and hygiene -- Canada -- History; Women -- Health and hygiene -- United States -- History; Women's health services -- Canada -- History; Women's health services -- United States -- History; Women's Health -- history; History, 19th Century; History, 20th Century; History, 21st Century; Women's Health Services -- history; Canada; United States; Femmes -- Santé et hygiène -- Canada -- Histoire; Femmes -- Santé et hygiène -- États-Unis -- Histoire; Femmes -- Soins médicaux -- Canada -- Histoire; Femmes -- Soins médicaux -- États-Unis -- Histoire; Médecine -- Histoire -- 19e siècle.; Médecine -- Histoire -- 20e siècle.; Médecine -- Histoire -- 21e siècle.; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; HISTORY -- North America; Women -- Health and hygiene; Women's health services; Canada; United States; History